Ukraine Humanitarian Response Plan 2023 - United Nations Office for the Coordination of Humanitarian Affairs (United Nations, 2024)
This document is consolidated by OCHA on behalf of the Humanitarian Country Team and partners. The Humanitarian Response Plan is a presentation of the coordinated, strategic response devised by humanitarian agencies in order to meet the acute needs of people affected by the crisis. It is based on, and responds to, evidence of needs described in the Humanitarian Needs Overview.